Antioxidant Capability and Physical Exercise in Neurobiology: A Focus in Neurodegeneration - Giorgia Scarfò; Simona Daniele; Ferdinando Franzoni (MDPI AG, 2021)
Neurodegeneration is a complex process controlled by both genetic and environmental factors [...]